(untitled) (Research, Society and Development, 2024)
This article presents the protocol for a scoping review, which aims to identify the impact of using the rapid molecular test for diagnosing tuberculosis among homeless people. The research question was formulated using the acronym PCC (population, concept and context): "What is the impact of using the rapid molecular test to diagnose tuberculosis among homeless people?". Controlled and free vocabularies will be used for the bibliographic survey in the following databases: EMBASE, Scopus, MEDLINE, Cinahl, Academic Search Premier, LILACS, Web of Science, Brazilian Digital Library of Theses and Dissertations, as well as Google Scholar. After the searches, the data will be exported to the Rayyan QCRI application, through which it will be possible to exclude duplicate publications and select the publications by having the titles and abstracts read by two independent reviewers. In a second selection stage, the eligible publications will be read in full. Before and after studies and time series studies will be included, as well as analytical observational studies, qualitative studies and opinion studies. The evidence presented will respond directly to the guiding question and the objective of the review and will be presented through a narrative synthesis, which, where appropriate, will be accompanied by tabulated results and/or graphs, which will map or describe the results found.